PROJECT MANAGEMENT IN THE CONSTRUCTION OF WATER RESERVOIRS AND PIPED IRRIGATION AS A CLEAN WATER SUPPLY SOLUTION FOR FARMERS IN PENANGGUNGAN VILLAGE, TRAWAS DISTRICT, MOJOKERTO REGENCY - Wuwuh Asrining Puri; Fatihatul Lailiyah; Edhi Soewartono (Sean Institute, 2025)
The availability of clean water is a major need for farmers in Penanggungan Village, Trawas District, Mojokerto Regency, who have been facing water shortages, especially during the dry season. This community service aims to overcome the problem of clean water shortages by managing the construction of water reservoirs and piped irrigation systems as a sustainable clean water supply solution. Because with the planning and construction of piped irrigation systems, it is expected that farmers can have easier, stable, and sustainable access to clean water. The methods used include integrated project management planning, active involvement of the community as partners, and application of simple technology that suits local conditions. This activity involved many farmers as the main participants and was carried out over several months with the stages of planning, implementation, and evaluation. The results of the service showed a significant increase in the availability of clean water that can be used for livestock needs and land irrigation, as well as increased community awareness and participation in water resource management. Thus, the construction of water reservoirs and piped irrigation makes a real contribution in supporting the sustainability of livestock businesses in the area.